Foam concrete landfill use in landslide hazardous area in west Şırnak road - Tosun, Yıldırım İsmail (IOS Press, 2014)
There are steeper slopes, sliding large land masses or rocks in Şırnak City and the surrounding areas. Underground water and harsh climatic conditions contain high risk hazard areas in urban living site with higher population density. In order to eliminate landslides and related events, significant precautions should be taken. The mapping of landslide risk may ease to take precautions. Even the application of landfill rock may reduce water content of soil. In this research, fly ash and Mine Waste shale stone were used with low density foam concrete. Waste mixture at certain proportions decreased cement use. Shale stone as fine aggregate instead of fly ash in specific proportions improved mechanical strength and porosity. Hence landslide hazardous area could be safer for urban living.
Keywords: Foam concrete; lightweight concrete; foam mortar; claystone